2019
DOI: 10.14814/phy2.13994
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the glucagon-like peptide 1 receptor agonist liraglutide on the streptozotocin-induced diabetic mouse kidney proteome

Abstract: In diabetes mellitus ( DM ), the kidneys are exposed to increased levels of hyperglycemia‐induced oxidative stress. Elevated amounts of reactive oxygen species ( ROS ) are believed to provoke ultrastructural changes in kidney tissue and can eventually result in DM late complications such as diabetic nephropathy. While it is reported that glucagon‐like peptide 1 receptors ( GLP ‐1R) are present in the kidney vasculature,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…revealed that liraglutide attenuates oxidative stress and albuminuria in streptozotocin (STZ)-diabetic rats via the PKA-mediated inhibition of renal NADPH oxidases ( Hendarto et al., 2012 ). Liljedahl et al performed label-free shotgun mass spectrometry (MS) and demonstrated that liraglutide increased the abundance of structurally involved proteins as well as proteins involved in oxidative stress responses in the kidney of STZ-induced diabetic mice ( Liljedahl et al., 2019 ). Moreover, it is reported that exendin-4 inhibits mesangial fibrotic responses ( Li et al., 2012 ; Xu et al., 2014 ).…”
Section: Renoprotective Mechanisms Of Glp-1rasmentioning
confidence: 99%
“…revealed that liraglutide attenuates oxidative stress and albuminuria in streptozotocin (STZ)-diabetic rats via the PKA-mediated inhibition of renal NADPH oxidases ( Hendarto et al., 2012 ). Liljedahl et al performed label-free shotgun mass spectrometry (MS) and demonstrated that liraglutide increased the abundance of structurally involved proteins as well as proteins involved in oxidative stress responses in the kidney of STZ-induced diabetic mice ( Liljedahl et al., 2019 ). Moreover, it is reported that exendin-4 inhibits mesangial fibrotic responses ( Li et al., 2012 ; Xu et al., 2014 ).…”
Section: Renoprotective Mechanisms Of Glp-1rasmentioning
confidence: 99%
“…In the in vivo experiment, the improved cardiomyocyte viability and increased autophagic flux were parallel with significantly decreased myocardial fibrosis and on a functional level with improved cardiac function as assessed by echocardiography [ 89 ]. The same molecular mechanisms resulting in the promotion of autophagy were also demonstrated in cultured hepatocytes and in the in vivo model of high-fat diet-fed C57BL/6 mice in which liraglutide significantly reduced the degree of liver steatosis [ 90 ]. In both cited experiments, chloroquine (an inhibitor of autophagy) promoted heart and liver injury, and these effects were also prevented by liraglutide [ 117 , 118 ].…”
Section: Glp1r Agonists As Antioxidative and Anti-inflammatory Agents In Other Tissues And Organsmentioning
confidence: 94%
“…The authors observed that STZ injection led to a significantly decreased content of catalase and glutathione peroxidase-3, enzymes critically involved in tissue protection against oxidative stress. The abundance of both enzymes was restored when animals with STZ-induced diabetes were concomitantly treated with liraglutide [ 90 ].…”
Section: Glp1ra As Antioxidative and Anti-inflammatory Agents In Dkd And Other Models Of Kidney Injurymentioning
confidence: 99%
“…Exendin-4 therapy resulted in a substantial reduction in all these lesions ( 167 ). In another similar mouse model, liraglutide resulted in restoration of catalase and glutathione peroxidase-3 levels, enzymes crucial in tissue protection against oxidative damage in kidneys ( 168 ).…”
Section: Summary Of Pulmonary Effects Of Glp-1mentioning
confidence: 99%